Clinical Evaluation of Ghana Shyam's TEFF (Telescopically Expanding Fixed Functional) Space Maintainer Versus Conventional Band and Loop Space Maintainer - Narra Venkata Krishna Raviteja; Madu Ghanashyam Prasad (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare the clinical efficacy of Ghana Shyam's TEFF space maintainer with band and loop space maintainer. Material and Methods: This split-mouth randomized clinical trial was conducted on 20 children (7-9 years), requiring bilateral/contralateral space maintenance therapy. After consent, all the selected children received both space maintainers and were followed up periodically every six months up to two years for clinical assessment according to the evaluation protocol. Instructions and motivation were given to the children. OHI (S) index was recorded before cementation of appliances. The following aspects were analyzed: 1) efficiency and function; 2) dislodgement due to cement loss; 3) breakage at soldered parts; 4) carious or gingival inflammation affecting abutment teeth; 5) distortion of band; 6) being embedded in gingival tissues / gingival slopping; and 7) initial and final S-OHIS scores. Statistical analysis was done using Fisher exact test for survival time and Chi-square test for chewing efficiency. Results: At 24th-month follow-up, 14 Ghana Shyam's TEFF space maintainers and 16 band and loop space maintainers were found to be intact. Conclusion: As both space maintainers demonstrated similar mean survival time Ghana Shyam's TEFF space maintainer with the added advantage of being functional can be recommended as an effective alternative to band and loop in premature loss of primary molar clinical situations.